(untitled) (Journal of actual problems of jurisprudence, 2024)
The article explores the phenomenon of the growth of radical Islamist movement in Central Asia. The aim of the work is to identify the key factors contributing to the spread of radical currents, the causes and methods are analysed. The study has important scientific and practical significance as it helps to understand the dynamics of radicalisation in the region. The methodology includes analysing the impact of economic, social and political conditions within the region that may contribute to the growth of religious radicalism, where aspects such as poverty, unemployment and social inequality are explored and their impact on the vulnerability of the population to radical ideologies. It explores how political instability and corruption in the region can contribute to the spread of radical ideologies. The authors examine how these factors affect public trust and stability. The article also focuses on the cultural and religious aspects that influence the rise of radical Islamism. The study includes an analysis of the interaction between traditional Islamic practices and radical ideas. The results show the influence of external and internal factors on radicalism. Particular attention is paid to the role of external forces, such as international Islamic organisations and global political interests, in the formation of radical currents in Central Asia. The authors also explore how the domestic politics of Central Asian states influence the rise of religious extremist currents. The paper makes a significant contribution to the understanding of this phenomenon. The article suggests strategies for countering radicalism, including international co-operation. It highlights the need for a thorough understanding of the causes of radicalisation in order to develop effective solutions. Key words: radical Islamism, Central Asia, extremism, terrorist organisations, international influence.